Sub-10 nm colloidal lithography for circuit-integrated spin-photo-electronic devices - Iovan, Adrian; Fischer, Marco; Lo Conte, Roberto; Korenivski, Vladislav (Beilstein Journal of Nanotechnology, 2012)
Patterning of materials at sub-10 nm dimensions is at the forefront of nanotechnology and employs techniques of various complexity, efficiency, areal scale, and cost. Colloid-based patterning is known to be capable of producing individual sub-10 nm objects. However, ordered, large-area nano-arrays, fully integrated into photonic or electronic devices have remained a challenging task. In this work, we extend the practice of colloidal lithography to producing large-area sub-10 nm point-contact arrays and demonstrate their circuit integration into spin-photo-electronic devices. The reported nanofabrication method should have broad application areas in nanotechnology as it allows ballistic-injection devices, even for metallic materials with relatively short characteristic relaxation lengths.
Keywords: magnetic point contact arrays; spin laser; sub-10 nm colloidal lithography